Utilization of Community Health Centers in Medicaid Expansion and Nonexpansion States, 2013–2014. Issue 4 (October 2016) - Hoopes, Megan J.; Angier, Heather; Gold, Rachel; Bailey, Steffani R.; Huguet, Nathalie; Marino, Miguel; DeVoe, Jennifer E.
Abstract : Using electronic health record data, we examined longitudinal changes in community health center (CHC) visit rates from 2013 through 2014 in Medicaid expansion versus nonexpansion states. Visits from 219 CHCs in 5 expansion states and 4 nonexpansion states were included. Rates were computed using generalized estimating equation Poisson models. Rates increased in expansion state CHCs for new patient, preventive, and limited-service visits (14%, 41%, and 23%, respectively, P < .01 for all), whereas these rates remained unchanged in nonexpansion states. One year after ACA Medicaid expansions, CHCs in expansion states saw an influx of new patients and provided increased preventive services.